Australian cardiac rehabilitation exercise parameter characteristics and perceptions of high-intensity interval training: a cross-sectional survey - Hannan AL; Hing W; Climstein M; Coombes JS; Furness J; Jayasinghe R; Byrnes J (Dove Medical Press, 2018)
Amanda L Hannan,1 Wayne Hing,1 Mike Climstein,2 Jeff S Coombes,3 James Furness,1 Rohan Jayasinghe,4–6 Joshua Byrnes7 1Faculty of Health Sciences & Medicine, Bond University, Gold Coast, QLD, Australia; 2Exercise Health and Performance Faculty Research Group, Faculty of Health Sciences, The University of Sydney, Sydney, NSW, Australia; 3School of Human Movement and Nutrition Sciences, The University of Queensland, Brisbane, QLD, Australia; 4Cardiology Department, Gold Coast University Hospital, Gold Coast, QLD, Australia; 5Griffith University, Gold Coast, QLD, Australia; 6Macquarie University, Sydney, NSW, Australia; 7Centre for Applied Health Economics, School of Medicine, Griffith University, Logan, QLD, Australia Purpose: This study explored current demographics, characteristics, costs, evaluation methods, and outcome measures used in Australian cardiac rehabilitation (CR) programs. It also determined the actual usage and perceptions of high-intensity interval training (HIIT).Methods: A cross-sectional observational web-based survey was distributed to 328 Australian CR programs nationally.Results: A total of 261 programs completed the survey (79.6% response rate). Most Australian CR programs were located in a hospital setting (76%), offered exercise sessions once a week (52%) for 6–8 weeks (49%) at moderate intensity (54%) for 46–60 min (62%), and serviced 101–500 clients per annum (38%). HIIT was reported in only 1% of programs, and 27% of respondents believed that it was safe while 42% of respondents were unsure. Lack of staff (25%), monitoring resources (20%), and staff knowledge (18%) were the most commonly reported barriers to the implementation of HIIT. Overall, Australian CR coordinators are unsure of the cost of exercise sessions.Conclusion: There is variability in CR delivery across Australia. Only half of programs reassess outcome measures postintervention, and cost of exercise sessions is unknown. Although HIIT is recommended in international CR guidelines, it is essentially not being used in Australia and clinicians are unsure as to the safety of HIIT. Lack of resources and staff knowledge were perceived as the biggest barriers to HIIT implementation, and there are inconsistent perceptions of prescreening and monitoring requirements. This study highlights the need to educate health professionals about the benefits and safety of HIIT to improve its usage and patient outcomes. Keywords: coronary artery disease, exercise, interval training, cardiovascular disease